Respiratory involvement and sleep-related disorders in CMT1A: case report and review of the literature - Massucco, Sara; Schenone, Cristina; Faedo, Elena; Gemelli, Chiara; Bellone, Emilia; Marinelli, Lucio; Pareyson, Davide; Pisciotta, Chiara; Mongini, Tiziana; Schenone, Angelo; Grandis, Marina (Frontiers in Neurology, 2024)
Sleep-disordered breathing has been reported in Charcot–Marie–Tooth disease (CMT) type 1A in association with diaphragmatic weakness and sleep apnea syndrome, mainly of the obstructive type (OSA). Improvement has been observed not only in sleep quality but also in neuropathy symptoms in CMT1A patients with OSA following the initiation of continuous positive airway pressure. We report the cases of two siblings affected by CMT1A associated with hemidiaphragm relaxatio necessitating nocturnal non-invasive ventilation (NIV). Two twins, now 42 years old, with a family history of CMT1A, received a genetic diagnosis of CMT1A at the age of 16. Over the years, they developed a slowly worsening gait disorder and a decline in fine motor hand movements, currently presenting with moderate disability (CMTES:13). At the age of 40, they both started complaining of daytime sleepiness, orthopnea, and exertional dyspnea. They received a diagnosis of relaxatio of the right hemidiaphragm associated with impairment of nocturnal ventilation and they both have benefited from nocturnal NIV. Disorders of breathing during sleep may be underestimated in CMT1A since routine investigations of sleep quality are rarely performed. Our two clinical cases and a literature review suggest the importance of inquiring about symptoms of excessive daytime sleepiness and respiratory disturbances in individuals with CMT1A, even in the absence of severe neuropathy. In the presence of compatible symptoms, a pneumological assessment, along with an overnight polysomnogram and lung function tests, should be performed. Recognizing sleep-related symptoms is essential for providing accurate treatment and improving the quality of life for patients with CMT1A.